(untitled) (Euro-Asia Conferences, 2021)
The article raises the issue of educating a comprehensively developed generation, which is one of the main social tasks of society, closely related to the activities of the family. And also the article talks about the importance of creating a physically strong, spiritually strong and intelligent healthy generation, which is the main task of the family. In this regard, the author emphasizes that the country pays great attention to strengthening the family and its upbringing, the spiritual well-being of the family, its place and importance for the stability of society.